Screening of plant growth promoting rhizobacteria (PGPR) to promote growth of soybean - Sri Widawati; Sulasih Sulasih (The East Java Biological Society, 2018)
Rhizobacteria is an essential component for the maintenance of soil fertility and plant growth. The objective of the study was to characterize plant growth promoting rhizobacteria (PGPR) activity such as phosphate solubilization, nitrogen-fixing, IAA production, Acc-deaminase and cellulase activity isolated from the rhizosphere and nodules of soybean and evaluate their effectiveness in stimulating soybean seedlings growth. Greenhouse assay was conducted by completely randomized design with three replications per treatment and two controls (K1-control without inoculation of bacteria and Nitrogen, K2-control inoculated with Bradyrhizobium japonicum. Pot experiments were conducted using sterile sand and supplemented with water and Muller solution, periodically. The results showed that nine rhizobacteria isolates were efficacious as potential PGPR. Greenhouse assay results showed that the highest vegetative growth yield was obtained in soybean inoculated with SWNC1 isolate, it was characterized as Bradyrhizobium spp. which gave the total nodules of 29.67; fresh weight of nodules of 0.61 g; nodules dry weight of 0.09 g; number of flowers of 23; plants dry weight of 5.57 g and plant height of 46 cm.